1999
DOI: 10.1106/vut6-tftt-frld-ubqr
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Magnetorheological Suspension for Seal

Abstract: Magnetorheological suspension (MRS) dispersing spherical several gm of iron particles in the low vapor pressure of dimethylpolysiloxane has been prepared. Yield stress has been proportional to square of magnetic field intensity and increases as containing larger volume fraction of iron particles and using solvent that is more viscous. The plastic viscosity increased linearly as a function of volume fraction of iron particles. The burst pressure of MRF seal is related on the dispersed iron particle size. The bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…A closer look at the structure of the MRF sealing reveals the reason for the leakage. The dynamic pressure of a MRF sealing consists of two components, as investigated in Fujita et al (1999). On one hand, the dynamic pressure is based on the magnetically induced yield stress of the particle chains.…”
Section: Tightnessmentioning
confidence: 99%
“…A closer look at the structure of the MRF sealing reveals the reason for the leakage. The dynamic pressure of a MRF sealing consists of two components, as investigated in Fujita et al (1999). On one hand, the dynamic pressure is based on the magnetically induced yield stress of the particle chains.…”
Section: Tightnessmentioning
confidence: 99%
“…The distance d between the magnetic poles and rotary shaft was fixed from 0.06 mm to 0.5 mm and from 1 mm to 1.7 mm, respectively. Fujitu et al [131] reported that the yield stress of MR suspension was proportional to the square of the magnetic field intensity and increased linearly with increasing volume fraction of iron particles and through the use of a more viscous solvent. In addition, the burst pressure of the MR suspension seal was reported to be related to the dispersed iron particle size.…”
Section: Mobile Sealmentioning
confidence: 98%
“…The magnitude of M s was determined by Fujitu et al [131] after achieving a magneto-fluidic composite. This includes iron microparticles and nanoparticles dispersed in a solvent (dimethyl polysiloxane).…”
Section: Mobile Sealmentioning
confidence: 99%
“…The study showed that critical pressure is proportionally related to the square of the applied magnetic field strength. Fujita et al [57] showed that the burst pressure of the seal is a function of size and the volume fraction of MRFs.…”
Section: Mrf Sealsmentioning
confidence: 99%